2017
DOI: 10.15640/ijhs.v5n2a4
|View full text |Cite
|
Sign up to set email alerts
|

Regional and Cultural Norms Shaping Substance Abuse, HIV and Hepatitis C Virus Risk and Prevention Needs among Minority Young Adults in A U.S.-Mexico Border Community

Abstract: Minority young adults in U.S.-Mexico border communities are at high risk for Substance Abuse(SA), and infection with the Human Immunodeficiency Virus (HIV) and Hepatitis C Virus (HCV). With funding from the Substance Abuse and Mental Health Services Administration (SAMHSA), a Hispanic Serving institution on the U.S.-Mexico border in partnership with two community-based organizations implemented integrated SA, HIV and HCV prevention among minority young adults on collegecampus and surrounding communities. Six f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Conditions unique to border populations, such as migration, language barriers, lack of access to health care, poverty, low health literacy, and structural violence (Pan American Health Organization, 2012), place individuals residing along the U.S.-Mexico border at increased risks for substance use, HIV, and HCV transmission, especially among minority young adults (Mangadu et al, 2017). A study examining HIV care along the California-Mexico border found that residents of Mexican origin and those who crossed the border frequently were less likely to have access to care due to stigma of being HIV positive, sick due to side effects, and concerned about others finding out about their status (Zuniga et al, 2008).…”
Section: Health Risks On Us-mexico Bordermentioning
confidence: 99%
“…Conditions unique to border populations, such as migration, language barriers, lack of access to health care, poverty, low health literacy, and structural violence (Pan American Health Organization, 2012), place individuals residing along the U.S.-Mexico border at increased risks for substance use, HIV, and HCV transmission, especially among minority young adults (Mangadu et al, 2017). A study examining HIV care along the California-Mexico border found that residents of Mexican origin and those who crossed the border frequently were less likely to have access to care due to stigma of being HIV positive, sick due to side effects, and concerned about others finding out about their status (Zuniga et al, 2008).…”
Section: Health Risks On Us-mexico Bordermentioning
confidence: 99%